Rectangular microstrip antenna design with multi-slotted patch and partial grounding for performance enhancement - Firoz Ahmed, Md; Muhammad Touhidul Islam, Abu Zafor; Hasnat Kabir, Md (International Journal of Electrical and Computer Engineering (IJECE), 2022)
This paper presents design of a rectangular microstrip patch antenna by using multi-slotted patch and partial grounding plane techniques for both the gain and bandwidth enhancement at the same time. The antenna is designed and simulated for ultra-wideband (UWB) applications using a high frequency structure simulator (HFSS) on FR4_epoxy substrate having a size of 30×20 mm with a dielectric permittivity of 4.4, a tangent loss of 0.02, and a thickness of 0.8 mm and excited by a simple 50 Ω microstrip feed line. The simulation results show that the antenna attains an improved gain of 8.06 dB with a wider impedance bandwidth of 19.7 GHz ranges from 3.15 to 22.85 GHz. The antenna also achieves an efficiency of 96.83% with a return loss of -28.35 dB, and a directivity of 9.39 dB within the entire frequency range. These results imply that the deployment of multi-slotted patch and partial grounding techniques in designing a rectangular microstrip patch antenna is effective in improving its performance.